Overcoming the barriers to the diagnosis and management of chronic fatigue syndrome/ME in primary care: a meta synthesis of qualitative studies - Bayliss, Kerin (BioMed Central, 2014)
BACKGROUND: The NICE guideline for Chronic Fatigue Syndrome/Myalgic Encephalomyelitis (CFS/ME) emphasises the need for an early diagnosis in primary care with management tailored to patient needs. However, GPs can be reluctant to make a diagnosis and are unsure how to manage people with the condition. METHODS: A meta synthesis of published qualitative studies was conducted, producing a multi-perspective description of barriers to the diagnosis and management of CFS/ME, and the ways that some health professionals have been able to overcome them. Analysis provided second-order interpretation of the original findings and developed third-order constructs to provide recommendations for the medical curriculum. RESULTS: Twenty one qualitative studies were identified. The literature shows that for over 20 years health professionals have reported a limited understanding of CFS/ME. Working within the framework of the biomedical model has also led some GPs to be sceptical about the existence of the condition. GPs who provide a diagnosis tend to have a broader, multifactorial, model of the condition and more positive attitudes towards CFS/ME. These GPs collaborate with patients to reach agreement on symptom management, and use their therapeutic skills to promote self care. CONCLUSIONS: In order to address barriers to the diagnosis and management of CFS/ME in primary care, the limitations of the biomedical model needs to be recognised. A more flexible bio-psychosocial approach is recommended where medical school training aims to equip practitioners with the skills needed to understand, support and manage patients and provide a pathway to refer for specialist input.